Development of an Electrical Lighting Installation Demonstration Tool Using a Triac-Based Light Sensor Switch - Wibowo, Salvo Eka; Anis, Samsudin; Arief, Ulfah Mediaty (Journal of Vocational and Career Education, 2024)
The automatic light sensor switch commonly used in the Electrical Power Installation Engineering Department at SMK Negeri 1 Tonjong is a factory-manufactured sensor switch with a complex circuit design, which has led to a decline in student learning motivation. This issue becomes the main reason for conducting research on the development of an instructional model for electrical lighting installations using a TRIAC-based light sensor switch, specifically applied in smart building lighting systems. This study employed a Research and Development (R&D) approach using the ADDIE development model. The findings of the study are as follows: (1) The developed product was deemed suitable for use, with a Content Validity Index (CVI) score of 0.88 from media experts and a Percentage of Agreement (PA) of 88%, and a CVI score of 0.91 and PA of 91% from subject material experts; (2) Product testing results indicated a high level of effectiveness, as shown by the Independent Sample t-Test on the N-gain Score, yielding a significance value (Sig. 2-tailed) of 0.000 < 0.05; and (3) The reproducibility coefficient (Kr) and scalability coefficient (Ks) were 92% and 81.5%, respectively, indicating that the instructional model for electrical lighting installation using the TRIAC-based light sensor switch is highly practical .